Dafydd Jones (ed.), Dada Culture. Critical Texts on the Avant-Garde 2006. - Bäckström, Per (Nordlit, 2007)
The Rodopi series Avant-Garde Critical Studies not only publishes books on neo-avant-garde but also studies of diverse aspects of the avant-garde in general. This new volume (no. 18), for example, is entirely dedicated to one of the most far-reaching avant-gardes in history, namely Dada. Although one cannot on the whole claim that a new book on Dada fills a gap, given that an enormous amount of research has been published over the years, nevertheless every contributionpresenting a new and clear view on the subject is welcome. In this book the focus is on the contemporary (theoretical) engagement with Dada, in an effort to show the actuality of the movement itself. Given the subtitle "Critical Texts on the Avant-Garde", however, it becomes relevant to note the problem inherent in such a formulation: a book on Dada contains critical texts on one avant-garde, but not on the avant-garde, a fact that is all the more conspicuous since David Cunningham points out in the concluding article that the expression "the avantgarde" is a post-war phenomenon (p. 272). However, the two excellent final articles point in many ways far beyond Dada, towards a rewritten theory of theavant-garde (which makes these articles alone worth the price of this volume); the preceding comment is therefore focused on the overall ambition of the volume, rather than the individual articles in themselves.
Keywords: Avant-Garde; Dafydd Jones; Dada Culture. Critical Texts on the Avant-Garde